Gay rights advocacies in Africa: the case of Ghana - Agyeman, Nana Kyeretwie (2017)
This thesis analyses international gay rights advocacies in Africa, using the country Ghana as a focal point. Gay rights by their mere sound, seem a concept that all should embrace without questions or qualms. Yet, there are not many concepts that have seen so much controversies, complexities and ironies than gay rights; especially in Africa. This thesis attempts to understand what gay rights are; how they have been received; and the reasons that underpin such receptions in an African country. It argues that, the intrinsic complexities embedded in gay rights advocacies require a cautious socio-legal unpacking beyond the easy and lazy racial stereotyping that currently characterises the debates. That systematic unpacking of the events of the (colonial) past and (postcolonial) present in order to make sense of the future is the central objective here. Using qualitative empirical evidence from primary and secondary sources, this thesis juxtaposes the philosophical realms of human rights theory, postcolonial theory and queer theory to the everyday and practical realities affecting gay people and stakeholders alike. It holds that, perhaps it is through engaging these theories holistically; and transposing them meaningfully to the contextual dispositions, could we make sense of the enormous issues (like the sources and effects of homophobia) that confront us.